Analisa Perbandingan Fungsi Efektivitas Cloud Management Platform OpenNebula Dan Eucalyptus - Haeruddin .; Agusyanto . (Universitas Internasional Batam, 2021)
Cloud Management Platform or CMP have an important role to provide maximum services for management device on premises and virtualization devices at utmost efficiency and under control. There are many types of CMP that can be use in any Cloud Computing Provider. However, choosing the right CMP, can provide accessibility on system management, such as expandability, cost, resource management, system durability and performance produced by the system. This analysis study is using Literature Review method to provide theoretical comparisons through the studies that have been researched by previous researchers. With this research study, Cloud Service Manager can choose the right CMP that suits their needs.